Kebijakan Deradikalisasi Dalam Rangka Penanggulangan Terorisme Dalam Pandangan Beberapa Stakeholder - Irawan, Anton; Runturambi, Arthur Josias Simon (Jurnal Kajian Stratejik Ketahanan Nasional, 2022)
Terrorism is a real threat to the state and society. Acts of terror that create widespread fear can have a negative impact on national security. One of the government's efforts to tackle terrorism is deradicalization. This study aims to view and analyse policies to combat or eradicate terrorism in perspective of some stakeholder. The method used is a qualitative method with data from literature studies and the publication of existing deradicalization programs. This study found that the main stakeholder with three stakeholder attributes such as power, legitimacy and urgency is the National Counterterrorism Agency (BNPT). However, social factors such as academics, society, religious and / or community leaders are also important stakeholders in the implementation of deradicalization. Keywords: Terrorism; Deradicalization, Stakeholder Analysis